Socio-Economic Factors Influencing Small-Scale Farmers’ Market Participation: Case of Rice Producers in Dano - Yaméogo, Thomas B.; Bossa, Yaovi Aymar; Torou, Bio M.; FUSILLIER, Jean Louis; Da, Dapola E. C.; Yira, Yacouba; Serpantié, Georges; Somé, Fourvouon; Dama-Balima, Mariam M. (My University, 2018)
This paper explores the key factors influencing market participation decisions among smallholder lowland rice growers. Data were collected through purposive sampling technique. A total of 127 rice growers, from 16 lowlands (developed and traditional lowlands), was selected. Descriptive statistics and the probit regression model were used to analyse the data. The statistical analysis revealed significant differences in yields between developed and traditional lowlands rice plots (“lowland development effect”). The regression results showed that farmers’ behaviours were not gender neutral; male producers were more likely to take part in the market as compared to their female counterparts, implying a “gender effect”. With respect to the effect of membership in farmers’ organization, the results indicate that farmers’ involvement in an organization, was in general negatively associated to their market participation decisions. However, farmers from lowlands with functional rice producers’ organizations were more likely to sell their products in the market. Interestingly, this study also highlighted that lowland rice producers’ ability to generate a marketable surplus (at least 20 kg/person/year) positively influence their market participation decision. As hypothesized, the results revealed that farmers who have access to potential buyers of the output (secured market outlets) were less likely to produce rice for self-consumption.
Keywords: developed lowlands; traditional lowlands; rice production; probit model; marketable surplus; Burkina Faso